A Literature Review on The Transformation of Defense Law in The Digital Age and Advanced Technology - Jaeni, Ahmad; Ignatius, Sinthu Bas; Karsoma, Ateng (The Future of Education Journal, 2025)
This study aims to examine the transformation of defense law in the digital age and advanced technology, focusing on the impact of technological advancements on national defense policies and regulations. With the rapid development of technology, particularly cyber threats that cross territorial boundaries, national defense legal systems face new challenges that require updates to regulations and policies. Through a literature review, this research identifies that traditional defense law needs to be revised to include protection of critical infrastructure, regulation of technology-based defense, and management of digital threats. Advanced technologies such as artificial intelligence, big data, and the Internet of Things provide opportunities to strengthen defense systems, but they also pose ethical and legal challenges, particularly regarding privacy, human rights, and accountability in the use of technology in military operations. The study also emphasizes the importance of international collaboration in addressing global transnational cyber threats. As a recommendation, countries need to urgently update their defense law regulations and strengthen international cooperation to maintain global security, while ensuring the use of defense technology aligns with international law principles and human rights.